POTENSI CERITA RAKYAT “KI AGENG MANGIR” SEBAGAI BAHAN AJAR PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Hari Kuncoro; Jeffry Handhika; Aris Wuryantoro (An Nafi': Multidisciplinary Science, 2026)
The integration of local wisdom through folklore into learning can strengthen students' character education in a contextual manner. This study aims to identify the character education values contained in the folk story "Ki Ageng Mangir" from Bantul Regency and analyze its potential as a teaching material for character education in elementary schools. This qualitative research uses content analysis and value analysis methods. Data were collected through document studies of the folk story text, interviews with cultural experts and elementary school teachers in Bantul, and analysis of relevant learning documents. Data were analyzed using an interactive model through data reduction, data presentation, and conclusion drawing. The findings reveal that the story of Ki Ageng Mangir contains strong character values, including nationalism (love for the homeland, courage in defending sovereignty), integrity (consistency of principles, responsibility), religious values, social care, and critical thinking skills in responding to conflicts and moral dilemmas. This folklore has great potential as character education material because it is geographically and culturally close to students, contains dramatic conflicts that are interesting for children, and presents complex character dilemmas that can trigger moral reasoning. This study concludes that the folklore of Ki Ageng Mangir can be effectively integrated into elementary school learning through various approaches, including storytelling, role-playing, and value analysis, to strengthen students' character education.